Continuous flow synthesis of micron size silica nanoparticles: parametric study and effect of dosing strategy - Jundale, Rajashri; Bari, Atul; Thara, Chinnu; Kulkarni, Amol (Journal of Flow Chemistry, 2018)
This work for the first time reports continuous flow synthesis of silica nano-particles of size over 1 mu m using a simple tubular reactor. The systematic approach involves the study of effect of various parameters like: ammonia concentration, water concentration, electrolyte concentraton, temperature, solvent, residence time and mode of TEOS injection over a wide range. A combination of ethanol and butanol was used as the medium with relatively lower polarity. Various process parameters were optimized to obtain highly monodispersed particles of size up to 600 nm and high yield (up to 90%). Attempts of reducing the reaction time by increasing temperature or concentrations of any of the reagents resulted in significant polydispersity and even in the formation of random shape agglomerates. At the optimized conditions almost complete conversion of TEOS happenned within 40 min and further growth of particles was achieved by adding TEOS using multipoint injection approach. While multipoint dosing resulted in the formation of very small number of secondary particles, the larger particles continued to grow beyond 800 nm. Further reduction in the polarity of reaction medium was achieved by adding 20% v/v of toluene, which without changing homogeneity of the solution resulted in particles as large as 0.9-1.1 mu m.
Keywords: Flow synthesis; Multipoint injection; silica; TEOS; Tubular reactor